Mentha piperita Oil Exerts an Antiepileptic Effect in Pilocarpine and Pentylenetetrazol-Induced Seizures in Mice - Waleed K. Abdulsahib; Sarmed H. Kathem; Mohanad Y. Al-Radeef; Layth S. Jasim (Veterinary Medicine International, 2022)
Introduction. Epilepsy is a progressive, chronic neurological disorder characterized by recurrent seizures. Peppermint (Mentha piperita L.) (MP) is one of the most commonly ingested herbal teas or tisanes with a single component. Aim. We aimed to assess the potential antiepileptic and neuroprotective features of MP essential oil (MPO) in pilocarpine (P) and pentylenetetrazol (PTZ) models of epilepsy. Methods. The study used eight groups of mice to assess the anticonvulsant activity of MPO in both the P and PTZ acute models in mice. P (350 mg/kg, i.p.) was given 30 minutes after MPO (1.6, 3.2, and 6.4 ml/kg, i.p.). As a positive control group, diazepam (1 mg/kg, i.p) was used. PTZ (95 mg/kg, i.p.) was given 30 minutes after MPO (6.4 ml/kg, i.p.). The first convulsion’s latency time, the number of convulsions, the latency time to death, and the percentage of deaths were calculated in all groups. Results. MPO significantly (P<0.05) increases the first convulsion’s latency time and the death’s latency time. Moreover, the essential oil significantly decreases the number of convulsions and reduces the mortality rate compared to the negative control group. Conclusion. MPO at 3.2 and 6.4 ml/kg doses can reduce the percentage and the number of convulsions and increase the latency time of both the first convulsion and death so that it can be used as a supplement in the treatment of epilepsy.